Endothelin-1-Induced Microvascular ROS and Contractility in Angiotensin-II-Infused Mice Depend on COX and TP Receptors - Christopher S. Wilcox; Cheng Wang; Dan Wang (MDPI AG, 2019)
(1) Background: Angiotensin II (Ang II) and endothelin 1 (ET-1) generate reactive oxygen species (ROS) that can activate cyclooxygenase (COX). However, thromboxane prostanoid receptors (TPRs) are required to increase systemic markers of ROS during Ang II infusion in mice. We hypothesized that COX and TPRs are upstream requirements for the generation of vascular ROS by ET-1. (2) Methods: ET-1-induced vascular contractions and ROS were assessed in mesenteric arterioles from wild type (+/+) and knockout (−/−) of COX1 or TPR mice infused with Ang II (400 ng/kg/min × 14 days) or a vehicle. (3) Results: Ang II infusion appeared to increase microvascular protein expression of endothelin type A receptors (ETARs), TPRs, and COX1 and 2 in COX1 and TPR +/+ mice but not in −/− mice. Ang II infusion increased ET-1-induced vascular contractions and ROS, which were prevented by a blockade of COX1 and 2 in TPR −/− mice. ET-1 increased the activity of aortic nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and decreased superoxide dismutase (SOD) 1, 2, and 3 in Ang-II-infused mice, which were prevented by a blockade of TPRs. (4) Conclusion: Activation of vascular TPRs by COX products are required for ET-1 to increase vascular contractions and ROS generation from NADPH oxidase and reduce ROS metabolism by SOD. These effects require an increase in these systems by prior infusion of Ang II.